Investigating use of daylight in a typical Algerian public classroom typology - Abdelhakeem, Mesloub (Penerbit UTM Press, 2015)
The presence of daylight affects human beings both physiologically and psychologically. Admitting daylight into an indoor enclosure improves mood, enhances morale, lowers fatigue, and reduces eyestrain. To adequately capture the characteristics of current daylight design practice in typical Algerian classroom A field observations was carried out in the study area which comprises the school buildings and including performing a series of measurements for daylighting inside the classrooms. This was further confirmed by the use of simulation using IES <VE> software. As investigated the standard sky condition in Algeria is overcast and based on this; the conceptual models of Algerian public schools are divided into two types of school buildings. Schools inherited from the colonial period and those built during the period of French occupation which are characterized by variation on the arrangements of classrooms even for a single school and are streamlined into; linear assembly with simple distribution (traditional classroom) which is common and the second type which has a linear assembly with double distribution. Based on the existing guideline from the Ministry of National Education which was adopted from the colonial masters. The simulation result confirm that class room typologies in Algeria had less consideration for climatic and comfort conditions and the window openings allowed excessive daylight.